Fågelbär (Prunus avium L.) : överlevnad, höjdutveckling och skador i unga planteringar på småländska höglandet - Roffey, Hampus (SLU/Dept. of Forest Ecology and Management, 2008)
Plant survival, plant damage and height growth were studied in nine wild cherry (Prunus avium L.) plantations in southern Sweden established between 2000 and 2002. All stands were located to the county of Småland. The survey was conducted during May and June in 2007. During the survey the height, diameter and quality of the cherry trees were recorded. In one stand, red – berried Elder (Sambucus racemosa L.) was a dominant species. In that stand the number of Elder bushes surrounding each cherry tree was recorded. Three of the stands were established on former forest land. The remaining six stands were established on sites previously used for agricultural purposes.